Awareness regarding the importance of vitamin D and prevention of its deficiency among female undergraduate medical students - Nowreen, Nida; Hameed, Reqaya (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Vitamin D deficiency is a common nutritional disorder that has assumed epidemic proportion. One of the major reasons for the worldwide spread of this disorder has been deficient awareness about the importance of vitamin D, its benefits on health, and prevention of deficiency state across different populations. Vitamin D deficiency (VDD) is widely prevalent in this part of the country (Kashmir valley, India), the prevalence being higher in females. This study was conducted to assess the awareness of female medical students regarding the importance of vitamin D and the prevention of its deficiency among them. Methods: This cross-sectional study was carried out among 113 female medical students. A self-administered questionnaire consisting of two parts was used to collect data. The first part was for identifying socio-demographic characters and the second half was a 12-question, multiple-choice survey focussing on vitamin D. Data was entered and analysed using computer software MS Excel. Results: The results of the study showed that the participants had good knowledge regarding some aspects while knowledge for other aspects was poor. The majority of participants had adequate knowledge about main source/dietary source of vitamin D, the site of synthesis, effect of vitamin D on bone health, main effects of deficiency on bone health, identification of high-risk groups and importance of supplements in management of deficiency. However, majority had inadequate knowledge about the epidemic state of VDD, RDA, time/duration of sun exposure and other effects of deficiency. Conclusions: The present study showed that there are some gaps in awareness about vitamin D, its benefits, and management of deficiency among female medical students.